Uma cartografia dos usos da noção de reanimação psíquica na psicanálise com bebês e crianças - Silva, Caroline Peixoto Mendonça (2013)
This research aims to investigate the uses of the Mental Resuscitation notion on child psychoanalysis. Understanding that this is a notion, recently created by the work of a French psychoanalyst in a neonatal resuscitation unity, and that others contemporary psychoanalysis authors also use this notion to describe divergent clinical phenomena, this study seeks to map the possible uses of this psychoanalytic notion considering the contexts where it can be applied, the public to whom it is intended, and what clinical phenomena the Mental Resuscitation notion is able to name. It was found through semi-open interviews with three child psychoanalysts, that the Mental Resuscitation notion can be used to describe the results of psychoanalytical intervention in cases of premature babies under intensive care, term infants under intensive care, babies with autistic symptoms, babies with phobic symptoms, handicapped babies and/or children, and in cases of non-decided child psychosis. It was also observed that the Mental Resuscitation notion can be used to designate psychoanalytical work with parents and the multiprofessional team responsible for taking care of the baby and/or child in a situation of organic or mental vulnerability, either at a clinical or a hospital context